BUSINESS INCUBATORS AS CATALYST FOR ENTREPRENEURIAL PROCESS DEVELOPMENT IN OYO AND EKITI STATES, NIGERIA - Musa Maigari; Bola O Jenyo; Alabi Qozim Diekola; Paul Zangu Terkula (Malete Journal of Accounting and Finance)
The study sought to examine business incubators as catalyst for entrepreneurial process development in Oyo and Ekiti States. The high rate of entrepreneurial failure rate in developing countries is motivation for this investigation to explore the relationship between business incubators and entrepreneurial process development in the target states. The population is made up of three hundred and forty-six (346) respondents made-up of technology incubators and staff of entrepreneurial start-ups and the sample of 186 was drawn from graduated residence incubates and technology incubator employees using Taro Yamane sample size calculation formula. The sampling approach employed was multistage sampling procedure through the use of purposive, stratified and simple random sampling technique to pick out respondents. Simple linear and correlation coefficient were used to test the hypotheses. The results confirmed that the impact of business incubators is a right predictor for entrepreneurial process development in Oyo and Ekiti States. The study concluded that business incubators are catalysts and essential tools for promoting entrepreneurial process development in Oyo and Ekiti states in South West Nigeria. The study recommends that authorities should intensify effort in equipping all TIC facilities in the country for better results and for incubates to seize the opportunity to increase their overall performance through the support services provided to them through business incubators